Innovative Evaluation: Uncovering the Need for Ethno- Stem Tools in Assessing Creative Thinking in Physics Education - Afifa, Mardiah; Wiyono, Ketang; Sriyanti, Ida (Edukasi, 2024)
This study investigated the need for an ethno-STEM-based assessment tool to evaluate creative thinking skills in prospective physics teachers. Data collection was conducted through a quantitative descriptive survey involving 53 first-year physics education students at Universitas Sriwijaya using Google Forms. The collected data were analyzed using Microsoft Excel to provide a comprehensive overview. The findings revealed that 81.13% of the participants hailed from South Sumatera, 96.23% expressed a preference for basic physics courses, and 98.11% recognized the importance of mastering creative thinking skills. Furthermore, 81.13% students indicated a strong demand for the development of ethno-STEM-based assessment tools. These results underscore the potential impact of culturally relevant assessment methods on fostering creative thinking in physics education. Integrating ethno-STEM into assessments not only enhances student engagement, but also cultivates essential creative thinking skills. Ultimately, this approach aims to build a more meaningful and effective physics education experience by bridging theoretical knowledge with students' cultural backgrounds and real-world applications, thereby supporting future educators in delivering impactful lessons.